Protection Mechanism of Clostridium butyricum against Salmonella Enteritidis Infection in Broilers - Zhao, Xiaonan; Yang, Jie; Wang, Lili; Lin, Hai; Sun, Shuhong (Frontiers in Microbiology, 2017)
This study was designed to evaluate the protection mechanism of oral administration of Clostridium butyricum against Salmonella enteritidis (SE) colonization in broilers. In the current study, 180 one-day-old healthy Arbor Acres (AA) broilers were meanly grouped into three, with three replicates of 20 birds each. An negative control group was fed basal diet without SE challenge and a positive control (PC) group was fed the basal diet and challenged with SE [106 colony forming unit (CFU)/0.2 mL]. An experimental (EXP) group was fed the basal diet, orally administered with C. butyricum (106 CFU/mL) and challenged with SE (106 CFU/0.2 mL). The results showed that compared to the PC group, the SE loads in livers, spleens, and cecal contents of chickens in EXP group were significantly reduced (P < 0.05) except in spleens at the 2-day post-infection; the production of interferon-γ, interleukin (IL)-1β, IL-8, and tumor necrosis factor-α in the livers, spleens, and cecal tissues of chickens in EXP group were decreased to different extents. The results of quantitative real-time polymerase chain reaction further revealed that the inflammation of chickens in EXP group was alleviated by C. butyricum via down-regulating TLR4, MyD88, and NF-κB-dependent pathways. Collectively, these findings indicated that oral administration of C. butyricum could be a suitable alternative for preventing SE infection in broilers.